Systemic Evaluation of the Effect of Diabetes Mellitus on Breast Cancer in a Mouse Model - Wei, Nana; Lu, Jinmiao; Lin, Zhibing; Wang, Xiaoyu; Cai, Mengmeng; Jiang, Shengyao; Chen, Xiaoyu; Zhu, Shilan; Zhang, Dong; Cui, Li (Frontiers in Oncology, 2022)
Breast cancer complicated with Diabetes mellitus (DM) is a common disease. To evaluate the effect of preexisting DM on breast cancer progression without drug interference, we use a streptozotocin (STZ)-induced Type 2 Diabetes mellitus BALB/c mice model. We found that 4T1 breast cancer complicated with DM decreased the mice survival time compared with 4T1 bearing mice. The diversity of gut microbiome was affected by DM. The infiltration of mucosal-associated invariant T cell (MAIT), CD8+ T cell and CD4+ T cell in the tumor was significantly decreased in DM-4T1 group compared with 4T1 group. The transcriptome data of tumor tissues indicated that the expressions of inflammatory C–C chemokines- and metabolism-related genes were greatly changed. The abnormal expression of these genes may be related with the decreased T cell infiltration in DM-4T1. In conclusion, the gut microbiome and tumor microenvironment of diabetic breast cancer patients have unique features. The effect of diabetes on breast cancer should be considered in the treatment for diabetic breast cancer patients.